Symposium 11: Developing and Delivering a Short Distance Learning Certificate Course in Peace and Reconciliation Studies – a Case Study - Courtney, Kathy (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes the development and implementation of a short distance learning course, entitled “Certificate in Peace and Reconciliation Studies”. It aims to illustrate how the development and final design of the course is the result of influences exerted by different stakeholders. Some of these interest groups have been able to influence course design directly at various stages, while the influence of others has been more indirect but still significant. The case study will show that it is not easy to achieve a ‘pure’ design, based on a specific pedagogical stance, but that in the end, design is based on compromise due to the influences of different stakeholders. A specific pedagogical stance – in this context a constructivist approach, carries with it expectations about the way students will be interacting with the course. The paper examines what expectations are embedded in the course design and explore to what extent the expectations have been realised.